Characteristics of children and adolescents with gender dysphoria for their health care: scoping review - Beatriz Peña; Melanie Catalina Pérez Orellana; Andrea Carolina Valenzuela Mena; Javiera Paz Aros Molina; Paula Ignacia González Núñez; Sofia Alejandra Castro Urra (Programa de Pós Graduação em Enfermagem da Universidade Federal do Piauí, 2024)
Objective: To identify the demographic and psychosocial characteristics of children and adolescents with gender dysphoria and of the health professionals involved in their care. Methods: Scoping review according to PRISMA-ScR with the databases Web of Science, Science Direct, Scopus, Virtual Health Library and Pubmed, using the descriptors: children, adolescents, gender dysphoria, pediatrics and health professionals. Inclusion criteria: primary and secondary research on gender dysphoria and sexual diversity in health care, with students or health professionals. Exclusion criteria: adult population, other context of health care, treatments, comorbidities and gray publication. Fifteen articles were included. Results: Children present with dysphoria around 6 years of age, with late diagnosis and treatment. They have a greater tendency toward mental health problems such as anxiety, depression and eating disorders, and family support is crucial. Health professionals have low undergraduate training, scarce continuous training and multidisciplinary work. Conclusion: It is necessary to incorporate subjects on diversity, gender identity and dysphoria into the training of health professionals, as well as continuous training with tools that allow a comprehensive approach, increasing confidence and security in the provider-patient relationship, in order to improve the well-being of children.